Proposed Layout Design of Production Facilities Using Group Technology To Improve Utility - Dimas Wahyu Fahturrohman; Wiwik Sumarni (Procedia of Engineering and Life Science, 2022)
PT. Behaestex Pandaan is a textile industry company in the field of weaving sarong products, at PT. This Behaestex Pandaan needs to regulate the placement of work stations with the aim that there is no unnecessary distance between two adjacent work stations due to unused space and the placement of work stations that affect the relationship of the production process. The method used is using rank order clustering (ROC) and process layout was chosen because as the best production floor layout design proposal that can be used for improvement at PT. Behaestex Pandaan.method Rank order clustering to provide displacement moments to improve the effectiveness of material flow.method Process layout for the preparation and placement of machines or production materials that have a similar model in one division. From the results of this study, it is proposed to be able to find out the best production floor layout proposal and the moment of its displacement, with the results of the initial layout being 16593316.22 meters every year, then using the process layout with the results of 6004001.39 meters every year, and the ROC method with a layout of 5314395.1 meters every year.